2021
DOI: 10.1523/eneuro.0453-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Optogenetic Stimulation of Primary Somatosensory Cortex and Its Projections to Striatum on Vibrotactile Perception in Freely Moving Rats

Abstract: Effects of optogenetic stimulation of primary somatosensory cortex and its projections to striatum on vibrotactile perception in freely moving rats

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
(73 reference statements)
0
10
1
Order By: Relevance
“…However, in other instances produced no identifiable effect (32). Furthermore, various optogenetic cell type stimulations of the S1 cortex and its projections bias (i.e., potentiate or suppress) somatosensory perception, whereas others did not affect perception at all (33). Based on this in our experiments, it would be unlikely that mice felt precisely the same interoceptive sensation in each optogenetic manipulation tested.…”
Section: Discussionmentioning
confidence: 57%
“…However, in other instances produced no identifiable effect (32). Furthermore, various optogenetic cell type stimulations of the S1 cortex and its projections bias (i.e., potentiate or suppress) somatosensory perception, whereas others did not affect perception at all (33). Based on this in our experiments, it would be unlikely that mice felt precisely the same interoceptive sensation in each optogenetic manipulation tested.…”
Section: Discussionmentioning
confidence: 57%
“…We hypothesized that FreiPose would be capable of detecting deviant behaviors caused by e.g., optogenetic stimulation. This capability would be particularly useful in control studies of optogenetic experiments because it is often required to test for unintended influences of the optogenetic stimulation (Aravanis et al, 2007; Gradinaru et al, 2009; Sun et al, 2021). To test whether FreiPose is suitable for detecting overt behavior during optogenetic stimulation, we injected rats unilaterally with a ChR2-carrying viral vector in the front paw area of the motor cortex.…”
Section: Resultsmentioning
confidence: 99%
“…In a series of experiments, we showcased possible applications of FreiPose. In an optogenetic experiment, we demonstrated that FreiPose can control for the unintended motor effects (Aravanis et al, 2007; Gradinaru et al, 2009; Ebina et al, 2019; Sun et al, 2021) of the stimulation. FreiPose enabled the quantification of overt movements due to optogenetic perturbations in the motor cortex with minimal additional experimental effort.…”
Section: Discussionmentioning
confidence: 97%
“…More than 10% of the initial radiation passed through the skin and skull samples. Since neurons involved in optogenetic stimulation are located in the brain cortex [66]- [68], this amount of irradiation should be sufficient for the actuation of phytochrome/opsins by two-photon absorption in the area of light-biotissue interaction. It is worth noting that an additional increase in the depth of penetration can be achieved using optical clearing methods [73], [74], but this is beyond the scope of research in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that the sample included a 1.5 mm brain which is characterised by high light absorption. However, the main optogenetic applications do not require a deep penetration into brain tissues, since the neurons involved in stimulation and monitoring are located in the brain cortex [66]- [68]. Therefore, the main aspect is the light transmittance through the skin and skull bone.…”
Section: B Transmission Measurements With Cw and Pulsed Lasersmentioning
confidence: 99%